Evaluating the Cross-Sectional and Longitudinal Relationships Predicting Suicidal Ideation Following Traumatic Brain Injury. Issue 1 (January 2021) - Awan, Nabil; DiSanto, Dominic; Juengst, Shannon B.; Kumar, Raj G.; Bertisch, Hilary; Niemeier, Janet; Fann, Jesse R.; Kesinger, Matthew R.; Sperry, Jason; Wagner, Amy K.
Abstract : Objective: Characterize relationships among substance misuse, depression, employment, and suicidal ideation (SI) following moderate to severe traumatic brain injury (TBI). Design: Prospective cohort study. Setting: Inpatient rehabilitation centers with telephone follow-up; level I/II trauma centers in the United States. Participants: Individuals with moderate to severe TBI with data in both the National Trauma Data Bank and the Traumatic Brain Injury Model Systems National Database, aged 18 to 59 years, with SI data at year 1 or year 2 postinjury ( N = 1377). Main Outcome Measure: Primary outcome of SI, with secondary employment, substance misuse, and depression outcomes at years 1 and 2 postinjury. Results: Cross-lagged structural equation modeling analysis showed that year 1 unemployment and substance misuse were associated with a higher prevalence of year 1 depression. Depression was associated with concurrent SI at years 1 and 2. Older adults and women had a greater likelihood of year 1 depression. More severe overall injury (injury severity score) was associated with a greater likelihood of year 1 SI, and year 1 SI was associated with a greater likelihood of year 2 SI. Conclusions: Substance misuse, unemployment, depression, and greater extracranial injury burden independently contributed to year 1 SI; in turn, year 1 SI and year 2 depression contributed to year 2 SI. Older age and female sex were associated with year 1 depression. Understanding and mitigating these risk factors are crucial for effectively managing post-TBI SI to prevent postinjury suicide. Abstract : Supplemental Digital Content is Available in the Text.